Novel approach to control CdS morphology by simple microwave-solvothermal method - Murugan, A. Vadivel; Kale, B. B.; Kulkarni, Aarti V.; Kunde, Lalita B.; Saaminathan, V. (2005)
Nanosize CdS powders with different microstructures are prepared in different solvents by using rapid microwave irradiation. Effect of solvents and Cd2+ precursors are to be able to control the particle size, and microstructures of CdS have been investigated by X-ray diffraction and TEM. The different particle size and morphologies are observed using different Cd2+ precursors in different solvents. TEM micrographs clearly show multiarmed nanorods and spherical shape morphologies of CdS powders are obtained in polar solvent like water (H2O), whereas non-polar polyol solvent like ethylene glycol (EG), prickle and cluster like morphologies of CdS are achieved with different Cd2+ precursors such as CdSO4 and Cd (CH3COO)(2). The spectroscopy studies of nanosize CdS are examined by photo-luminescence spectra. Band gap and the absorption co-efficient for nano CdS is also evaluated from optical absorption studies. (C) 2005 Springer Science + Business Media, Inc.